2017
DOI: 10.1038/sj.bdj.2017.839
|View full text |Cite
|
Sign up to set email alerts
|

An estimated carbon footprint of NHS primary dental care within England. How can dentistry be more environmentally sustainable?

Abstract: Introduction National Health Service (NHS) England dental teams need to consider from a professional perspective how they can, along with their NHS colleagues, play their part in reducing their carbon emissions and improve the sustainability of the care they deliver. In order to help understand carbon emissions from dental services, Public Health England (PHE) commissioned a calculation and analysis of the carbon footprint of key dental procedures.Methods Secondary data analysis from Business Services Authorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
61
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 7 publications
0
61
0
1
Order By: Relevance
“…This was the highest percentage of the total carbon emissions in NHS primary Dental Care, in England. 8 In 2018 PHE wrote the report Carbon modelling within dentistry, towards a sustainable future. Comparing the 2013/14 data with now, new academic studies have shown that global carbon dioxide emissions dropped roughly 17% during the forced confinement (not dental specific).…”
Section: What Does the Law Say?mentioning
confidence: 99%
See 1 more Smart Citation
“…This was the highest percentage of the total carbon emissions in NHS primary Dental Care, in England. 8 In 2018 PHE wrote the report Carbon modelling within dentistry, towards a sustainable future. Comparing the 2013/14 data with now, new academic studies have shown that global carbon dioxide emissions dropped roughly 17% during the forced confinement (not dental specific).…”
Section: What Does the Law Say?mentioning
confidence: 99%
“…patients to attend an appropriate number of appointments, reducing their overall travel and surgery time. 8 In the current climate, using public transport is a more uncomfortable thought for many. Car sharing has always been suggested as an appropriate means of reducing a carbon footprint -but that now is fraught with uncertainty -single car occupancy feels much safer.…”
Section: Composite Disposal and The Environmentmentioning
confidence: 99%
“…In England, the average water consumption of a dental practice is estimated at around 33 thousand litres per surgery each year. 34 Although this water use and the treatment of waste water contributes only 0.09% (587 tonnes of CO2e) to the total carbon footprint of primary NHS England dental services, water is becoming more scarce and needs to be conserved. 29 Dental practices could undertake similar interventions as households to reduce water consumption.…”
Section: Water Consumptionmentioning
confidence: 99%
“…The stakeholders and agencies involved in the design of the dental environment are only just starting to understand that sustainable healthcare within dental practice is integral to patient's overall health and well‐being and, therefore, closely linked to its code of ethics and professionalism. The carbon footprint for dentistry has now been calculated in several countries with two‐thirds of carbon emissions originating from travel, one‐seventh from energy, and one‐fifth from procurement . The dental‐related travel burden contributes to the worsening air quality directly affecting the respiratory and cardiovascular health of our population, which equates to a loss of around 14 quality adjusted life minutes per person every year…”
mentioning
confidence: 99%
“…Identify a passionate team member to be a “sustainability champion” and communicate what you are doing widely with staff, patients, and via social media or websites. The emerging research within dentistry indicates that, although it will take time to build a sufficient evidence base, this is the time to start simply and gradually build on the change using freely available e‐learning tools designed to help you better design your own dental environment …”
mentioning
confidence: 99%